Suppression of In Vivo Neovascularization by the Loss of TRPV1 in Mouse Cornea - Katsuo Tomoyose; Yuka Okada; Takayoshi Sumioka; Masayasu Miyajima; Kathleen C. Flanders; Kumi Shirai; Tomoya Morii; Peter S. Reinach; Osamu Yamanaka; Shizuya Saika (Journal of Ophthalmology)
To investigate the effects of loss of transient receptor potential vanilloid receptor 1 (TRPV1) on the development of neovascularization in corneal stroma in mice. Blocking TRPV1 receptor did not affect VEGF-dependent neovascularization in cell culture. Lacking TRPV1 inhibited neovascularization in corneal stroma following cauterization. Immunohistochemistry showed that immunoreactivity for active form of TGFβ1 and VEGF was detected in subepithelial stroma at the site of cauterization in both genotypes of mice, but the immunoreactivity seemed less marked in mice lacking TRPV1. mRNA expression of VEGF and TGFβ1 in a mouse cornea was suppressed by the loss of TRPV1. TRPV1 gene ablation did not affect invasion of neutrophils and macrophage in a cauterized mouse cornea. Blocking TRPV1 signal does not affect angiogenic effects by HUVECs in vitro. TRPV1 signal is, however, involved in expression of angiogenic growth factors in a cauterized mouse cornea and is required for neovascularization in the corneal stroma in vivo.